Polyamine Synthesis Effects Capsule Expression by Reduction of Precursors in Streptococcus pneumoniae - Ayoola, Moses B.; Shack, Leslie A.; Nakamya, Mary F.; Thornton, Justin A.; Swiatlo, Edwin; Nanduri, Bindu (Frontiers in Microbiology, 2019)
Streptococcus pneumoniae (pneumococcus, Spn) colonizes the human nasopharynx asymptomatically but can cause infections such as otitis media, and invasive pneumococcal disease such as community-acquired pneumonia, meningitis and sepsis. Although the success of Spn as a pathogen can be attributed to its ability to synthesize and regulate capsular polysaccharide (CPS) for survival in the host, the mechanisms of CPS regulation are not well-described. Recent studies from our lab demonstrate that deletion of a putative polyamine biosynthesis gene (ΔcadA) in Spn TIGR4 results in the loss of the capsule. In this study, we characterized the transcriptome and metabolome of ΔcadA and identified specific mechanisms that could explain the regulatory role of polyamines in pneumococcal CPS biosynthesis. Our data indicate that impaired polyamine synthesis impacts galactose to glucose interconversion via the Leloir pathway which limits the availability of UDP-galactose, a precursor of serotype 4 CPS, and UDP-N-acetylglucosamine (UDP-GlcNAc), a nucleotide sugar precursor that is at the intersection of CPS and peptidoglycan repeat unit biosynthesis. Reduced carbon flux through glycolysis, coupled with altered fate of glycolytic intermediates further supports impaired synthesis of UDP-GlcNAc. A significant increase in the expression of transketolases indicates a potential shift in carbon flow towards the pentose phosphate pathway (PPP). Higher PPP activity could constitute oxidative stress responses in ΔcadA which warrants further investigation. The results from this study clearly demonstrate the potential of polyamine synthesis, targeted for cancer therapy in human medicine, for the development of novel prophylactic and therapeutic strategies for treating bacterial infections.